A Randomized Clinical Trial of Snus Examining the Effect of Complete Versus Partial Cigarette Substitution on Smoking-Related Behaviors, and Biomarkers of Exposure. Issue 4 (11th April 2019) - Meier, Ellen; Lindgren, Bruce R; Anderson, Amanda; Reisinger, Sarah A; Norton, Kaila J; Jensen, Joni; Strayer, Lori; Dick, Laura; Tang, Mei-Kuen; Chen, Menglan; Carmella, Steven G; Hecht, Stephen S; et al.
Abstract: Introduction: This 8-week multisite, randomized controlled trial of snus examined the differential effects of instructions on (1) snus use, (2) smoking and smoking-related measures, and (3) exposure to tobacco-related constituents. Method: US adult daily cigarette smokers ( n = 150; 43.3% female; Medianage = 43.5) were recruited from Minneapolis, Minnesota; Columbus and Coshocton, Ohio; and Buffalo, New York. Following a 1-week sampling phase of snus, participants who used at least 7 pouches were randomized to either (1) partial substitution (PS; "use snus as you like with your cigarettes"), (2) complete substitution (CS; "avoid cigarettes"), or (3) usual brand cigarettes (UB). Analyses included between-group analyses (eg, PS vs. CS) using Wilcoxon rank sum test of cigarettes per day and snus pouches per day, and a linear mixed model (biomarkers). Results: Compared to the PS and UB groups, smokers assigned to CS reported greater reductions in cigarettes per day ( ps < .001), using more snus pouches per day ( p = .02), and more smoke-free days (CS median = 14.5, PS and UB medians = 0, p < .001). In addition, results demonstrated reductions in carbon monoxide ( p < .001), total nicotine equivalents ( p = .02), and four out of five measured volatile organic compounds ( ps < .01) over time among the CS group. Exposure to N ′-nitrosonornicotine increased by trial end only among the PS group ( p < .04). Phenanthrene tetraol increased among all groups by trial end ( p = .02) with no difference between groups. Conclusions: Instructions to completely switch from cigarettes to snus resulted in the greatest reduction in cigarettes and exposure to harmful constituents. Implications: Directly instructing smokers to switch completely to snus, rather than using ad libitum (with no instructions to avoid cigarettes), is necessary for reductions in smoking and subsequent exposure to harmful constituents.